Analysis of Erosive Nature of Fruit Beverages Fortified with Calcium Ions: An In Vitro Study Evaluating Dental Erosion in Primary Teeth. (9th June 2022) - Dedhia, Priyanka; Pai, Deepika; Shukla, Shyam Dutt; Anushree, U.; Kumar, Saurabh; Pentapati, Kalyana C
Abstract : Background . Since children frequently consume acidic fruit beverages, dental erosion is common in children. The erosive effects on primary teeth are more profound due to the lesser thickness of enamel and dentin. This study evaluated if calcium fortification of fruit beverages could reduce their erosive potential. Methodology . Tropicana Orange Delight was the fruit beverage chosen and fortified with calcium carbonate. Forty noncarious extracted primary teeth were equally distributed into four groups. Samples in group A were exposed to calcium-fortified fruit beverages and group B to nonfortified fruit beverages for 1, 2, and 3 min. The pH and calcium ion concentration of both the fruit beverages were evaluated from baseline through the test period. Samples in groups C and D were then exposed to fortified and nonfortified fruit beverages for 10, 20, and 30 min. The surface roughness and microhardness of these samples were analysed. Results . Due to fortification, the pH and calcium ion concentration of fortified beverages was higher compared to nonfortified beverages at baseline. The calcium ion concentration of fortified beverages decreased from baseline in contrast to an increase in the nonfortified beverage group. This indicates that fortified beverage is less erosive in nature. The surface roughness of samples in the fortified beverage group did not decrease significantly from baseline. In the nonfortified beverage group, surface roughness values at 20 and 30 min of exposure were higher than baseline, suggesting that significant erosive changes occur at the prolonged duration of exposure. The microhardness values of samples in the fortified beverage group increased from baseline through the test period, suggestive of resistance to erosion offered by calcium fortification. The microhardness values of samples in the nonfortified beverage group decreased through the test period, suggestive of erosion. Conclusion . Calcium fortification of this fruit beverage significantly reduces its erosive potential on primary teeth.